Gross Structure and Biometry of Ovary in Kadaknath and White Leghorn Breeds of Fowl - Kumar, Dinesh; Vaish, R; Bhardwaj, JK; Pandey, Y; Gupta, N; Rajput, N (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A Gross morphologic and biometric study was conducted on ovaries of a total 72 female chicks/ growers, 36 each of Kadaknath and White Leghorn (WLH) breeds. The birds were grouped according to age into 6 (I-VI) groups, viz., 1, 4, 8, 12, 16 and 20 weeks old. The gross observations revealed that the left ovary was elongated triangular with base directed rostrally and conical apex caudally in all the groups of Kadaknath and WLH, except in age group V and VI of WLH. The mean weight of the ovary in age group I was 0.08±0.01g and 0.08±0.18 g, which increased to 0.31±0.04 g and 21.17±2.29 g in Kadaknath and WLH, respectively. The mean length of ovary in Kadaknath was 0.68±0.03 cm in age group I, which increased to 2.02±0.09 cm in age group VI. The mean length of ovary was slightly more in WLH than Kadaknath group I, which became more than twice in age group VI.